Pemikiran Fazlur Rahman Mengenai Politik Islam - Ryzka Dwi Kurnia (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2021)
Fazlur Rahman is a thinker of Islamic neo-modernism who wants to actualize the teachings of Islam in a unified and solid framework, where one aspect and the other are interrelated. Through this approach, he wants the Qur'an to be understood in an integral and total way, so that things that are considered contradictory no longer exist. This effort is his obsession so that humans can capture the messages of the Qur'an holistically. Departing from his concern for the global problems facing Muslims, he offers a solution that is grounded in the differences between normative Islam and historical Islam. From this distinction, Fazlur Rahman conducted a comprehensive reconstruction of Islamic scholarship. The reconstruction he did refers to the original and definite Islam. For this reason, he suggested that the Qur'an as the main source of Islam needs to be interpreted as a whole and not to interpret it fragmentarism (paragraph verses), namely an interpretation that is able to understand the Qur'an as a whole, so that the theological, legal, political aspects and ethics in the teachings of the Qur'an into a unified whole. Fazlur Rahman argues that the purpose of the Qur'an is to establish an ethical and egalitarian society. So, Islamic society is formed because of Islamic ideology. The ideal condition of the Islamic social order is "which calls for good and prevents evil". This is in order to realize the implementation of politics based on Islamic ideology which cannot be separated from the Qur'an and Sunnah.